Valorization of dairy waste and by-products through microbial bioprocesses. (February 2022) - Usmani, Zeba; Sharma, Minaxi; Gaffey, James; Sharma, Monika; Dewhurst, Richard J.; Moreau, Benoît; Newbold, John; Clark, William; Thakur, Vijay Kumar; Gupta, Vijai Kumar
Graphical abstract: Highlights: Dairy waste is a great source of biodegradable feedstock for sustainable production. Microbes can valorize whey waste from dairy into bioplastics and biosurfactants. Dairy waste is a beneficial substrate to culture microbes for biofuel production. Integrated strategies for dairy waste valorization can drive sustainable growth. Abstract: Waste is an inherent and unavoidable part of any process which can be attributed to various factors such as process inefficiencies, usability of resources and discarding of not so useful parts of the feedstock. Dairy is a burgeoning industry following the global population growth, resulting in generation of waste such as wastewater (from cleaning, processing, and maintenance), whey and sludge. These components are rich in nutrients, organic and inorganic materials. Additionally, the presence of alkaline and acidic detergents along with sterilizing agents in dairy waste makes it an environmental hazard. Thus, sustainable valorization of dairy waste requires utilization of biological methods such as microbial treatment. This review brings forward the current developments in utilization and valorization of dairy waste through microbes. Aerobic and anaerobic treatment of dairy waste using microbes can be a sustainable and green method to generate biofertilizers, biofuels, power, and other biobased products.